APPLICATION OF THE PROBLEM BASED LEARNING MODEL WITH SPINNING WHEEL MEDIA IN IMPROVING UNDERSTANDING OF SCIENCE CONCEPTS: PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN MEDIA SPINNING WHEEL DALAM PENINGKATAN PEMAHAMAN KONSEP IPAS - Intan Devia Maharani; Siti Masfuah; Wawan Shokib Rondli (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aimed to analyze the difference in the mean scores of students’ understanding of Integrated Science and Social Studies (IPAS) concepts and to measure the improvement in conceptual understanding after the implementation of the Problem Based Learning (PBL) model assisted by the Spinning Wheel media. This quantitative study employed a pre-experimental method using a one-group pretest–posttest design. The research was conducted in a fourth-grade class at SD 4 Gondangmanis involving 21 students as the research subjects. The dependent variable was students’ conceptual understanding of IPAS, while the independent variable was the implementation of the Problem Based Learning (PBL) model with the Spinning Wheel media. Data were collected through observation, interviews, documentation, and tests. The data were analyzed using the Normality Test, Paired Sample t-Test, and N-Gain Test with SPSS version 26. The results of the Paired Sample t-Test showed a significance value of 0,00 (0,00 < 0,05), indicating a significant difference between students’ pretest and posttest scores. This finding demonstrates that the implementation of the Problem Based Learning (PBL) model assisted by the Spinning Wheel media significantly improved students’ conceptual understanding of IPAS. Furthermore, the N-Gain score was 0,6965, which falls into the moderate improvement category. Therefore, it can be concluded that the Problem Based Learning (PBL) model assisted by the Spinning Wheel media effectively enhances fourth-grade students’ conceptual understanding of IPAS.